ANTIOXIDANT AND LARVICIDAL ACTIVITIES OF Pistacia lentiscus FRUIT ESSENTIAL OIL - Khedidja AMIRA; Nour El-Houda DJEGHADER (Journal of Animal and Plant Sciences, 2026)
Pistacia lentiscus or mastic tree, a medicinal plant from Anacardiaceae family, is widely used in Algerian traditional medicine for its therapeutic properties. This study aimed to extract essential oil (EO) from its dried fruits by hydrodistillation using a Clevenger apparatus and determine its yield of extraction. The antioxidant activity of the EO was evaluated using the 2,2-diphenyl-1-picrylhydrazyl(DPPH) method, with ascorbic acid (AA) as a positive control, at concentrations of 0.25, 0.5, 1.0 and 2.0 µg/ml. In addition, its insecticidal activity was tested against third and fourth instar larvae of Culex pipiens at concentrations of 5, 10, 15, and 25 µl/ml. The EO yield was 0.4%, consistent with values reported in previous studies. Antioxidant tests showed significant radical scavenging activity, with inhibition ranging from 45.91 to 68.46% compared with 49.52 to 73.31% for AA, and Inhibition concentration IC₅₀ values were 0.62 µg/ml and 0.12 µg/ml for the two samples respectively. Larvicidal assays revealed concentration-dependent mortality, meaning that higher concentrations caused higher mortality in both larval stages, with lethal concentrations LC₅₀ and LC₉₀ values estimated at 10 and 27 µl/ml for third instar larvae; 17 and 32 µl/ml for fourth instar larvae, respectively. These findings demonstrated that P. lentiscus fruit EO possesses promising antioxidant and larvicidal properties, suggesting its potential applications in natural pest control and health-related fields.
Keywords: Pistacia lentiscus; essential oil; hydrodistillation; antioxidant activity; larvicidal activity.